Integrating the Spirit of Educators into the Cultivation of Normal University Students: Value, Realistic Dilemma and Path Choice - GAO Song; SHEN Shilong (Jiaoshi jiaoyu xuebao)
In the context of building a powerful education system, the spirit of educators, as a spiritual cornerstone for fostering high-quality and professionalized teachers, embodies profound value connotations and demonstrates an intrinsic logical alignment with the cultivation of normal university students. Systematic analysis reveals that integrating the educator spirit into student cultivation inherently corresponds to the holistic development of normal university students. It unifies their cognitive understanding, emotional engagement, ideological conviction, and practical implementation. Nevertheless, this integration process currently encounters persistent challenges, primarily manifested in three dimensions. They are insufficient institutional coordination in strategic planning for embedding the educator spirit into curricula and training systems, a deficiency in exemplary role modelling by educators to authentically demonstrate the spirit, and inadequate comprehension of its core tenets among students. To address these issues, a tripartite collaborative framework is imperative. Universities must spearhead systematic institutional planning. Educators should exemplify the spirit through ethical and pedagogical practices. Students must engage in self-cultivation encompassing both personal virtues and professional competencies. Such an integrative approach will establish a robust foundation for nurturing future educators with advanced professionalism and comprehensive excellence.